Diaspora Remittance as a Form of Sustainable Finance: Case Studies in Underdeveloped and Developing Countries - Abdihakin Mohamoud Ibrahim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Diaspora remittances are a major and relatively stable external financing source for underdeveloped and developing countries, often surpassing aid and foreign direct investment. Drawing on a narrative review of recent empirical studies, meta-analyses, and country cases, this paper examines how remittances contribute to sustainable finance by affecting economic growth, poverty and inequality, financial inclusion, and environmental outcomes. The evidence shows that remittances generally reduce poverty and enhance financial inclusion, while their growth and environmental impacts are heterogeneous and depend on factors such as financial development, human capital, and institutional quality. The paper argues that targeted policies lowering transaction costs, strengthening and digitizing financial systems, and designing instruments to channel remittances into productive and green investments are essential to fully integrating remittances into national sustainable finance and development strategies.